Peningkatan Partisipasi dan Hasil Belajar IPA Melalui Penerapan Metode Kerja Kelompok - Rahimi Rahimi (JURNAL PENA EDUKASI, 2018)
Abstract: The purpose of this research is to increase students' learning achievement and learning outcomes on the material to identify the properties of objects based on observation including solid objects, liquid by applying the method of group work. Research subjects of students in grade IV as many as 20 students. The results showed an increase in learning participation from 20% at baseline to 80%, and at the end of the second cycle to 100%, as well as the increase in the average grade continued to increase from 57.00 at baseline to 66.00 in cycle first, and at the end of the second cycle to 76.00, with a 10% improvement of learning completeness at baseline, to 50.00%, and in the last cycle to 100%. Based on the results of research can be concluded that the use of the application of methods of group work can increase the participation and student learning outcomes on subjects IPA students on the material to identify the properties of objects based on observations including solid objects, liquid. Keywords: participation, learning outcomes, group work, solid objects, liquids Abstrak: Tujuan dari penelitian ini untuk meningkatkan partisipasi dan hasil belajar IPA siswa pada materi mengidentifikasi sifat-sifat benda berdasarkan pengamatan meliputi benda padat, cair dengan menggunakan penerapan metode kerja kelompok. Subjek penelitian siswa kelas IV sebanyak 20 siswa. Hasil penelitian menunjukan peningkatan pada partisipasi belajar dari 20% pada kondisi awal menjadi, 80%, dan pada akhir siklus kedua menjadi 100%, serta peningkatan nilai rata-rata kelas terus mengalami peningkatan dari 57,00 pada kondisi awal menjadi 66,00 pada siklus pertama, dan pada akhir siklus kedua menjadi 76,00, dengan peningkatan ketuntasan belajar 10% pada kondisi awal, menjadi 50,00%, dan pada siklus terakhir menjadi 100%. Berdasarkan hasil penelitian dapat disimpulkan bahwa penggunaan penerapan metode kerja kelompok dapat meningkatkan partisipasi dan hasil belajar siswa pada mata pelajaran IPA siswa pada materi mengidentifikasi sifat-sifat benda berdasarkan pengamatan meliputi benda padat, cair. Kata kunci: partisipasi, hasil belajar, kerja kelompok, benda padat, benda cair